(untitled) (Baghdad Science Journal, 2025)
This research presents a theoretical method to calculate the mismatch factor for the PV module. Within this study the effect of mismatch on I-V and P-V of the module is observed. In practice, the PV panel module consists of 36 cells connected in series part that is built into PSPICE (from previous work) is used for this study. The PV modules are wired in a long series string in most of PV applications; the performance will be disproportionately limited by any one module that is not producing as much power. Fortunately, by changing the system configuration it is possible to isolate losses so that entire arrays are not affected by poor performance in one module. So, in this work the mismatch effect has been tested for series and parallel wiring of the modules, the parallel configuration produced significantly the same power as mismatch arises on the array.